Twenty-Fifth International Symposium on Fault-Tolerant Computing. Digest of Papers
DOI: 10.1109/ftcs.1995.466967
|View full text |Cite
|
Sign up to set email alerts
|

Node covering, error correcting codes and multiprocessors with very high average fault tolerance

Abstract: Abstract-Structural fault tolerance (SFT)is the ability of a multiprocessor to reconfigure around faulty processors or links in order to preserve its original processor interconnection structure. In this paper, we focus on the design of SFT multiprocessors that have low switch and link overheads, but can tolerate a very large number of processor faults on the average. Most previous work has concentrated on deterministic k-fault-tolerant (k-FT) designs in which exactly k spare processors and some spare switches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, deriving optimal graphs G ′ with minimal links any general graph G has exponential complexity. To the best of the authors' knowledge, optimal solutions are found only on regular graphs such as lines, square-grids, circles, and trees [2,15,18].…”
Section: Minimum Redundant Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, deriving optimal graphs G ′ with minimal links any general graph G has exponential complexity. To the best of the authors' knowledge, optimal solutions are found only on regular graphs such as lines, square-grids, circles, and trees [2,15,18].…”
Section: Minimum Redundant Linksmentioning
confidence: 99%
“…At a fundamental level, there are methods to construct topologies for redundant nodes that address both nodes and links reliability [2,15]. Based on some input graph, additional links (or, bandwidth reservations) are introduced optimally such that the least number is needed.…”
Section: Related Workmentioning
confidence: 99%
“…Most of hardware redundancy reconfiguration techniques rely on complex algorithms to re-assign physical resources to the elements of the logical array. In most cases these algorithms are executed by a central processor which also performs diagnosis functions and co-ordinates the reconfiguration of the physical array [6] [12] [8]. This approach has demonstrated to be effective, but its centralised nature makes it prone to collapse if the processor in charge of the fault tolerance functions fails.…”
Section: The Present Approach To Fault Tolerance In Processor Arraysmentioning
confidence: 99%
“…1. I have developed a range of novel and efficient methodologies for designing fault-tolerant multiprocessors that include use of covering graphs and graph automorphisms, and a structural application of error correcting codes (ECCs) to yield multiprocessors with very high average fault tolerance [11,17,23,24,25,27,69,71,76,77,78,79]. In 1995, one of these papers [79] (published in 1988) was awarded the recognition of a most influential paper published in the first 25 years, 1971-1995, of the premier conference on fault-tolerant computing, the Fault Tolerant Computing Symp.…”
Section: Fault-tolerant Computingmentioning
confidence: 99%